Rock Phosphates and Phosphate Solubilizing Microbes as a Source of Nutrients for Crops - Grover, Richa (My University, 2007)
Phosphorous is second only to nitrogen as an essential macronutrient for plant growth and development (Scheffer et al., 1998). Soils are often high in insoluble mineral and organic phosphates but deficient in available orthophosphate (Pi) (Dadarwal et al., 1997). Soil amendment with phosphatic fertilizer, produced via chemical processing of rock phosphate ore, is therefore an absolute requirement in order to feed the world's population. For over one hundred years, workers have recognized the ability of soil microorganisms to solubilize Pi from insoluble (i.e. nutritionally unavailable) organic and mineral phosphates (Whitelaw, 2000). Wide ranges of microbial biosolubilization mechanisms exist, so that much of the global cycling of insoluble organic and inorganic soil phosphates is attributed to bacteria and fungi. The genetic and biochemical mechanisms for this solubilization are as varied as the spectrum of P-containing soil compounds. For over one hundred years, workers have recognized the ability of soil microorganisms to solubilize Pi from insoluble (i.e. nutritionally unavailable) organic and mineral phosphates (Whitelaw, 2000). Wide ranges of microbial biosolubilization mechanisms exist, so that much of the global cycling of insoluble organic and inorganic soil phosphates is attributed to bacteria and fungi. The genetic and biochemical mechanisms for this solubilization are as varied as the spectrum of P-containing soil compounds. The limiting level of Pi in most soils provides the ecophysiological basis for positioning associations between plant roots and mineral phosphate solubilizing (MPS) and/or organic P solubilizing microorganisms. These associations are assumed to play an important role in phosphorus nutrition in many natural and agro-ecosystems. As a result, an enormous amount of research has been conducted involving isolation and characterization of MPS and organic P solubilizing microorganisms from a wide range of soils. In general, the goals have been to understand P cycling and/or to develop P biofertilizers analogous to biological nitrogen fixation. To date the results of these efforts have been problematic.
Keywords: Nutrients for Crops; Solubilizing Microbes; PSMS; Immobilized Cell Technology